Method statement for earthwork / Nur Aina Akmal Mohd Noor - Mohd Noor, Nur Aina Akmal (Universiti Teknologi MARA, Perak, 2013)
This report briefly describes the processes and methods that involves in earthwork. It is produced according to a five-month experience in the construction field especially in project site. This report is divided into four sections and start with the background of the company as well as background of the construction project. The finding of earthwork process in this observation was not easy as it expected. It involves a lot of machineries and manpower. It also has specified the sequence of work starting with acceptance of tender to handover of a completed project. In this report, it is described the nature of work undertaken for earthwork. Then, this report is highlighted the machines that used in earthwork. Subsequently, this report is described in more detail about each of the sequences that involved in earthwork. During earthwork process, some of the problems associated with earthworks have been identified and the report ended with some suggestion that felt able to solve the identified problems. In conclusion, this report could explain in more detail about the process and methods used for earthwork process to readers.